Abnormal Wear Mechanism and Improvement of High-Speed Cylindrical Roller Bearing. (26th July 2021) - Zhang, Wenhu; Deng, Sier; Zhang, Song; Wang, Jian; Zheng, Jintao
Abstract : This paper presents the dynamic differential equations of cylindrical roller bearing, considering the dynamic unbalance mass of roller and the contact between the roller end face and the inner ring rib. The influence of bearing working condition and structural parameters on the P V value of roller end face and the slip speed of roller working surface were analysed. The theoretical analysis and experimental results both show that the large amount of roller's dynamic unbalance mass due to the difference in chamfering size on both sides of the roller and the deviation of the bearing axial clearance are the main causes of abnormal wear on the roller working surface and end face.